Ад’єктивно-іменні словосполучення на позначення статичних джерел звуку: метонімічний ракурс (на матеріалі сучасної німецької мови) - Блажко, Марія Іванівна; Blazhko, M. I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті концептуалізація відношень між статичним джерелом звука та його властивостями пояснюється за допомогою метонімії як внутрішньоконцептної процедури репрезентації звучання. Встановлено, що звучання осмислюється за допомогою просторової й об’єктної метонімії. Просторова метонімія сприяє осмисленню ситуації продукування звуку джерелом, яке перебуває в певному місці, а об’єктна метонімія відбиває розпізнавання джерела звуку як цілого за його ознаками або частинами, втілюючись у трьох моделях сполучуваності прикметників та дієприкметників на позначення звучання з іменниками на позначення частин тіла й артефактів. The article reveals the role of metonymy as a procedure, performed within a concept, in the conceptualization of relations between a static sound source and its qualities. It is found that in modern German these relations are verbalized by adjectival-nominal word combinations, reflecting a static way of understanding the source of sound. It is proved that the metonymic conceptualization of sound production is represented be spatial and object relations. The spatial metonymy contributes to understanding the situation of sound production by a source situated in a particular place while the object metonymy reflects the process of recognizing a sound source conceptualized as a whole, relying on its features or parts. The reconstructed models of the combinability of the adjectival units under study with nouns rest on the following types of reasoning processes: 1) characterizing a sound with respect to the way of its production; 2) the state of a person revealed with the help of a sound; 3) the source of sound reflecting its qualities; 4) qualities of a sound with reference to its source.
German Adjectival-Nominal Phrases Denoting Static Sound Sources: Metonymic Perspective
Keywords: ад’єктивно-іменні словосполучення; adjectival-nominal phrases; ад’єктивні одиниці на позначення звучання; adjectival units denoting sound; концептуальна метонімія; conceptual metonymy